Rheo logical properties of dough and bread quality characteristics as influenced by the proportion of wheat flour substitution with orange-fleshed sweet potato flour and baking conditions - Chikpah, Solomon Kofi; Korese, Joseph Kudadam; Hensel, Oliver (LWT Food Science Technology, 2021)
This study investigated the influence of wheat flour substitution with 10–60% of peeled or unpeeled orangefleshed sweet potato (OFSP) flour on dough rheological properties as well as the effects of the flour mixture, baking temperature (150–200 ◦C) and time (15–25 min) on the physical and textural properties of the composite bread. I-optimal (combined) design of the Design-Expert software was used for the experimental design whereas the flour mixture and baking conditions for wheat-OFSP composite bread formulation were optimized using the response surface methodology. Significant models were developed where lack-of-fit was insignificant (p > 0.05), coefficient of determination, R2 and adjusted R2 were greater than 0.90 for all response variables of the dough and bread. Farinograph optimum water absorption decreased whereas dough development time increased with increased OFSP flour addition. Moreover, increasing OFSP flour, baking temperature and time significantly (p < 0.05) decreased loaf volume, specific volume, crumb water activity, crust and crumb lightness, crumb springiness, cohesiveness and resilience whereas crust and crumb redness, hardness and chewiness increased. The substitution of wheat flour with 29.4 or 28.0% of peeled or unpeeled OFSP flour, respectively and baking at 180 ◦C for 15 min produced optimum dough and bread quality characteristics.
Keywords: Baking conditions; Composite bread; Dough rheological properties; Orange-fleshed sweet potato; Textural properties; University of Development Studies; Water & irrigation; Ghana; ACE: Water, Irrigation and Sustainable Agriculture